Internet resources for neurosurgeons and neuropathologists. Issue 2 (1st February 2003) - Thomson, S; Phillips, N
Abstract : Neurosurgical and neuropathological resources on the internet are rapidly developing. Some excellent clinical, patient information, professional, academic, and teaching web sites are available. This review summarises the most useful online sites for neurosurgeons and neuropathologists in the United Kingdom and beyond. More general internet resources have been covered in the first article in this series.